2010
DOI: 10.1007/s00425-010-1325-4
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of somatic embryos and regeneration of plants from primordial shoots of 10-year-old somatic white spruce and expression profiles of 11 genes followed during the tissue culture process

Abstract: Adult conifers are notoriously recalcitrant in vegetative propagation and micropropagation that would result in the regeneration of juvenile propagules through somatic embryogenesis (SE) has not been demonstrated to date. Because SE-derived material is more amenable in subsequent tissue culture experiments compared with seed-derived material, a multi-year study was conducted to investigate induction of SE from primordial shoot (PS) explants that were excised from shoot buds of somatic embryo-derived white spru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 46 publications
(51 reference statements)
11
67
0
3
Order By: Relevance
“…The expression pattern of CmWUS during embryogenesis was in agreement with that of orthologous genes in Coffea canephora and L. decidua (Nic-Can et al 2013;Rupps et al 2016). The WUS gene contributed to promoting the transformation of somatic cells into embryogenic cells and the maintenance of embryogenesis, and might be considered as a putative embryo marker to predict the embryogenic potential (Zuo et al 2002;Klimaszewska et al 2011). Therefore, taken with the high expression during the early stage, it is believed that the role of CmWUS is to perform a function of maintaining competency of embryogenesis.…”
Section: Expression Of Embryogenesis-related Genes During Somatic Embsupporting
confidence: 49%
See 1 more Smart Citation
“…The expression pattern of CmWUS during embryogenesis was in agreement with that of orthologous genes in Coffea canephora and L. decidua (Nic-Can et al 2013;Rupps et al 2016). The WUS gene contributed to promoting the transformation of somatic cells into embryogenic cells and the maintenance of embryogenesis, and might be considered as a putative embryo marker to predict the embryogenic potential (Zuo et al 2002;Klimaszewska et al 2011). Therefore, taken with the high expression during the early stage, it is believed that the role of CmWUS is to perform a function of maintaining competency of embryogenesis.…”
Section: Expression Of Embryogenesis-related Genes During Somatic Embsupporting
confidence: 49%
“…The WUS gene, belonging to WUSCHEL-related homeobox (WOX) gene family, plays a key role in early somatic embryo development (Zuo et al 2002;Wang et al 2009). Known WOX2, as a putative marker, is supposed to be a possible function regulating differentiation of embryos (Palovaara and Hakman 2008;Klimaszewska et al 2011). Evidence has indicated that LEC genes appear to act as a pivotal part in the early and late stages of embryogenic development (Jia et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Somatic embryogenesis induction was obtained for two out of the three tested genotypes, and its frequencies ranged up to 3.4% and 50.7% for individual genotypes. Recently, Klimaszewska et al (2011) reported somatic embryogenesis from primordial shoot explants for Picea glauca excised from the shoot buds of 10-year-old somatic embryo-derived trees. The somatic embryogenesis induction frequency ranged from 7 to 82% for five tested clones using this type of explant.…”
Section: Micropropagation By Somatic Embryogenesismentioning
confidence: 99%
“…У арабидопсиса экспрессия гена WUS слу-жит маркером и стимулятором СЭ и участвует в закладке ПАМ у соматических зародышей (Chen et al, 2009;Su et al, 2015); ген WOX5, в свою очередь, участвует в закладке КАМ соматических зародышей (Su et al, 2015). На разных видах растений показано, что в соматических зародышах также экспрессируются гомологи генов WOX2 (Gambino et al, 2011;Klimaszewska et al, 2011;Rupps et al, 2016) и WOX9 (Kurdyukov et al, 2014). Гомологи генов WOX1 и WOX3, функционирующих в ходе развития листа, акти-вируются на поздних стадиях СЭ у Vitis vinifera (Gambino et al, 2011).…”
Section: каллусообразование и соматический эмбриогенез: творческий поunclassified